Determination of the inhibitory effects of N-methylpyrrole derivatives on glutathione reductase enzyme - Esma Kocaoğlu; Oktay Talaz; Hüseyin Çavdar; Murat Şentürk; Claudiu T. Supuran; Deniz Ekinci (Taylor & Francis Group, 2019)
Glutathione reductase (GR) is a crucial antioxidant enzyme which is responsible for the maintenance of antioxidant GSH molecule. Antimalarial effects of some chemical molecules are attributed to their inhibition of GR, thus inhibitors of this enzyme are expected to be promising candidates for the treatment of malaria. In this work, GR inhibitory properties of N-Methylpyrrole derivatives are reported. It was found that all compounds have better inhibitory activity than the strong GR inhibitor N,N-bis(2-chloroethyl)-N-nitrosourea, especially three molecules, 8 m, 8 n, and 8 q, were determined to be the most powerful among them. Findings of our study indicates that these Schiff base derivatives are strong GR inhibitors which can be used as leads for designation of novel antimalarial candidates.